Quality Control in HR Management: Ensuring Accreditation in Higher Education - Baharun, Hasan; Khomairotusshiyamah, Unzilah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
The aim of this research is to analyze more deeply the implementation of the Quality Control concept in Human Resources (HR) management in higher education, as well as its influence on the sustainability of accreditation quality. In this research, several methods were used to produce findings from the research, namely conducting interviews with related parties, such as the Chancellor or Rectorate, lecturers, administrative staff, as well as the Coordinator or Head of the Study Program. to collect data related to the implementation of a data-based Quality Control system in monitoring lecturer suitability standards, teaching quality and human resource welfare. The results of this research show that effective implementation of Quality Control can increase openness and continuous monitoring of HR performance, which can provide support for meeting accreditation standards and improving the quality of education. The impact of this research is the importance of structured and data-based human resource management in order to directly ensure the sustainability of accreditation quality in higher education, as well as strengthening quality management practices that are easily adaptable to developments and can adjust according to educational needs.